2018
DOI: 10.1093/humrep/dey083
|View full text |Cite
|
Sign up to set email alerts
|

Does human endometrial LGR5 gene expression suggest the existence of another hormonally regulated epithelial stem cell niche?

Abstract: STUDY QUESTIONIs human endometrial leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5) gene expression limited to the postulated epithelial stem cell niche, stratum basalis glands, and is it hormonally regulated?SUMMARY ANSWER LGR5 expressing cells are not limited to the postulated stem cell niche but LGR5 expression is hormonally regulated.WHAT IS KNOWN ALREADYThe human endometrium is a highly regenerative tissue; however, endometrial epithelial stem cell markers are yet to be confirmed. LGR5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 45 publications
(75 reference statements)
3
68
0
Order By: Relevance
“…The basalis markers described below (SSEA-1, nuclear SOX9, nuclear β-catenin) were the first basalis markers to be presented as epithelial ASC markers in 2013 [ 13 ]. Subsequent work has also suggested N-cadherin to be another basalis marker [ 84 ], but the very recent work using LGR5 in situ hybridisation challenges this hypothesis and proposes the existence of more than one epithelial stem cell niche in the human endometrium [ 85 ]. These studies, however, are based on the presumption that human endometrial glandular architectural arrangement is a single blunt-ended tube, which is disputed in 3D reconstruction studies [ 86 ].…”
Section: Identifying Markers That Are Expressed By Cells Located Imentioning
confidence: 99%
See 3 more Smart Citations
“…The basalis markers described below (SSEA-1, nuclear SOX9, nuclear β-catenin) were the first basalis markers to be presented as epithelial ASC markers in 2013 [ 13 ]. Subsequent work has also suggested N-cadherin to be another basalis marker [ 84 ], but the very recent work using LGR5 in situ hybridisation challenges this hypothesis and proposes the existence of more than one epithelial stem cell niche in the human endometrium [ 85 ]. These studies, however, are based on the presumption that human endometrial glandular architectural arrangement is a single blunt-ended tube, which is disputed in 3D reconstruction studies [ 86 ].…”
Section: Identifying Markers That Are Expressed By Cells Located Imentioning
confidence: 99%
“…However, this study has not demonstrated any other stem cell properties of the SSEA1 + epithelial cells and their in vivo tissue reconstitution ability is also not yet known. More recent work has described some SSEA1 + cells to also be located in the LE, thus the expression is not strictly limited to the basalis [ 85 ]. The other criticism of SSEA1 + cells being progenitors is their relative abundance in the basalis and in the PM endometrium.…”
Section: Identifying Markers That Are Expressed By Cells Located Imentioning
confidence: 99%
See 2 more Smart Citations
“…TCGA contained RNA sequencing data with patient follow up data for n = 200 of LGEC (grade I and II endometrioid EC) and n = 281 of HGEC (grade III endometrioid, serous, undifferentiated EC). Published microarray datasets from 3 further individual studies were examined with Illumina’s BaseSpace Correlation Engine application in BSCA and genes that perturbed AGR2 gene when mutated knocked down were identified with the Knockout atlas application as previously described [ 50 ] software; https://www.illumina.com/informatics/research/biological-data-interpretation/nextbio.html ; Illumina, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%